A concepção de educação ambiental adotada nos estabelecimentos de ensino de Santa Helena PR - Sterchile, Adriela (2016)
The Environmental Education (EE) has as one of its finalities to stimulate knowledge and actions that promote the reflexion upon the existent relationship between society and environment. Many are the researchers that dedicate to this finality, which enhance the need for continuous improvement on EE. In this sense, this research aims to analyse EE comprehension used at the teaching establishments at the town of Santa Helena PR, in a way to identify which is the concept of formal EE adopted by the participants that justifies and characterises the environmental culture of the town, and discuss the means of access and implantation of EE at the teaching establishments. For that, we opt with the use of document research techniques and questionnaires. In this research we searched to evaluate if the existent environmental practices at the studied establishments meet the prevised actions at ProNEA National Program of Environmental Education, by meaning categories, guided by the Bardin Content Analysis technique (2011). Such categories were elaborated from three macro tendencies in EE, proposed by Layrargues e Lima (2011): Conservationist Tendency, Pragmatic Tendency and Critic Tendency. As such, it was possible to notice that the participant educators are managing to overcome the ecological vision of EE, toning down the promotion of disconnected practices based on the change of individual behaviour or empathy with nature. But this overcoming is still on the theoretical plane, since they don t demonstrate confidence in assuming more critical postures regarding EE teaching. However, they still cannot transpose these ideas for their actions on school routine.